How to open my eyes? The performance-lecture as a method within artistic research - Cerezo, Bel (Networking Knowledge: Journal of the MeCCSA Postgraduate Network, 2016)
This paper presents and examines my research/work How to open my eyes? as a case study attempting to highlight the tactic of the performance-lecture as an important critical method within artistic research. As a brief definition, the performance-lecture is a hybrid and heterodox form what contains performative and discursive components. Since the 1990s the performance-lecture is gaining prominence within contemporary artistic practices and the number of visual and performance artists that use this format is growing. However, David Ladnar noted that despite its ubiquity, the notion of the performance-lecture is still contested and the bibliography on it is short. Within this context, and focusing on artistic research, the aim of this paper is to analyse how the performance-lecture operates as a method that generates new knowledge, drawing on the interrogation of the research/work How to open my eyes? produced practice-led PhD enquiry, on some of the bibliography on the format of the performance-lecture and on my experience as a part of the audience of several performance-lectures.